2020
DOI: 10.1002/htj.21754
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigation on capture of CO2 and other pollutants from an SI engine using the physical adsorption technique

Abstract: Carbon dioxide (CO2) is considered as a major contributor to global warming. Automobile contributes to around 65% of total carbon dioxide emissions globally when compared with other sources. On considering the upcoming stringent emission norms, this problem needs to be addressed properly. In this proposed study, an attempt is made to capture CO2 and other emissions from spark ignition engines using activated carbon as an adsorbent. In the initial part of this study, a numerical investigation on backpressure wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Therefore, the outlet pressure is regarded as the atmospheric pressure (i.e., 0 N/m 2 ). The velocity of engine exhaust is viewed as the inlet velocity (i.e., 24 m/s), which is measured with the help of an anemometer.The flow analysis through porous material is determined by the direction vector, permeability, and inertial losses [8].…”
Section: Vvoid Represents Void Volume;mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the outlet pressure is regarded as the atmospheric pressure (i.e., 0 N/m 2 ). The velocity of engine exhaust is viewed as the inlet velocity (i.e., 24 m/s), which is measured with the help of an anemometer.The flow analysis through porous material is determined by the direction vector, permeability, and inertial losses [8].…”
Section: Vvoid Represents Void Volume;mentioning
confidence: 99%
“…Mohankumar Subramaniam et al [8] examined numerical and experimental investigation in spark ignition (SI) engine to capture exhaust emissions using activated carbon. The material's porosity is modified and located at three locations to determine the optimum backpressure and maximum filtration efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…emissions for the specified engine load are plotted and explained below. The complete burning of fuel increases CO 2 emissions [11]. Figure 9 depicts the relationship between CO 2 emissions and engine load.…”
Section: Emission Characteristicsmentioning
confidence: 99%
“…In these materials, there is no electron transfer between CO 2 , and the adsorbent and molecules are preferentially adsorbed onto the surface of adsorbents. 11 Owing to their high CO 2 capture, zeolites are widely regarded as the main materials for CO 2 adsorption applications. 12 In a previous study, the H-ZSM-5 demonstrated CO 2 adsorption of 2.6 mmol g −1 at 273 K, at 1 bar under flue gas conditions.…”
Section: Introductionmentioning
confidence: 99%